Therapeutic Potential of Quercetin in Diabetic Neuropathy and Retinopathy: Exploring Molecular Mechanisms - Saikia, Lunasmrita; Aziz Barbhuiya, Sm Abdul; Saikia, Kalyani; Kalita, Pratap; Dutta, Partha Pratim (Current Topics in Medicinal Chemistry, 2024)
Diabetes mellitus poses a significant health challenge globally, often leading to debilitating complications, such as neuropathy and retinopathy. Quercetin, a flavonoid prevalent in fruits and vegetables, has demonstrated potential therapeutic effects in these conditions due to its antioxidant, anti-inflammatory, and neuroprotective properties. This review summarizes and provides a comprehensive understanding of the molecular mechanisms underlying the efficacy of quercetin in ameliorating diabetic neuropathy and retinopathy. A thorough search was carried out across scientific databases, such as SciFinder, PubMed, and Google Scholar, to gather pertinent literature regarding the effect of quercetin on diabetic neuropathy and retinopathy till February 2024. Preclinical studies indicate that quercetin mitigates neuropathic pain, sensory deficits, and nerve damage associated with diabetic neuropathy by improving neuronal function, reducing DNA damage, regulating pro-inflammatory cytokines, enhancing antioxidant enzyme levels and endothelial function, as well as restoring nerve injuries. In diabetic retinopathy, quercetin shows the potential to preserve retinal structure and function, inhibiting neovascularization, preventing retinal cell death, reducing pro-inflammatory cytokines, and increasing neurotrophic factor levels. Moreover, through modulating key signaling pathways, such as AMP-activated Protein Kinase (AMPK) activation, Glucose Transporter 4 (GLUT 4) upregulation, and insulin secretion regulation, quercetin demonstrates efficacy in reducing oxidative stress and inflammation, thereby protecting nerve and retinal tissues. Despite promising preclinical findings, challenges, such as limited bioavailability, necessitate further research to optimize quercetin’s clinical application in order to establish its optimal dosage, formulation, and long-term efficacy in clinical settings.
Keywords: Anti-oxidant